Penciptaan Nilai Logistik Pelabuhan di Indonesia - Cahya Purnomo; Suyanti Suyanti (Majalah Ilmiah Bahari Jogja, 2019)
This paper highlights the creation of Indonesian ports logistics value, by review relevance journals. The finding are taht Indonesian ports faces problems, i.e policy concern to national logistics, transportation's infrastructure, availability of cargo, skill concern logistics. There are 3 (three) port logistics value : serial activity, pooled activity, and reciprocal activity. The activities of each actor in the port are getting better and better integrated. While there is no synchronization of flow of goods that enter and exit of the port.